Enduring Entrepreneurship in the Context of Public-Private Partnerships - Pittz, Thomas G.; White, Rebecca (Journal of Strategic Innovation and Sustainability, 2016)
As institutional innovations designed to effect societal change, this work considers public-private partnerships (PPPs) as exemplars of enduring entrepreneurship. By surviving beyond the initial objectives of the partnership, many PPPs exhibit continual renewal and repeated acts of entrepreneurship as they explore novel solutions to intractable social problems. With recognition of goal interdependence between partner firms and a structure of open governance, PPPs create unique opportunities for innovative ideas and knowledge exploration and exploitation. This manuscript explores the formative conditions of PPPs and suggests two important outcomes - enhanced absorptive capacity and knowledge spillovers – that contribute to enduring entrepreneurship and long-lasting partnerships.